Efectos de las condiciones psicosociales en el desempeño laboral del personal profesional de enfermería del hospital general Teófilo Dávila - Sánchez Apolo, Blanca Flor (2017)
The present research aims to identify the effects of psychosocial conditions at the job performance of professional nursing staff of the Hospital General Theophilus Davila, the non-experimental study based on a cross-sectional descriptive methodology , it worked with a sample of 62 nurses of the emergency areas, surgical center , gynecology and internal medicine .At the conclusion of the work and analyze the data obtained from surveys indicates that stay in touch with the pain, suffering the 14.51% (62 nurses) have emotional fatigue, in what refers to the depersonalization that is the direct result of the emotional exhaustion; the results obtained from the application of the Maslach test in the study population, The 17.74% present a risk of depersonalisation, affecting the female gender, personal fulfillment the 98.38% has a high level, which indicates that it is not affected this dimension; in the development of the activities of the nursing care process, the 100% of users indicates respect for their privacy, the 86.15 % has been with the care received, as well as the 89% are satisfied with the information received in the course of his hospitalization by the nursing staff.